PENENTUAN HARGA JUAL AMPLANG PADA ANISA AMPLANG DI SAMARINDA - Elfreda Aplonia Lau, Zahrah Bibi. M, Lca. Robin Jhonathan (EKONOMIA, 2015)
The purpose of this study was to determine the percentage increase in selling price per pack amplang set by Enterprises. Formulation of the problem in this study Is amplang pricing sell for Rp 10,000, - per set Ons Enterprises Anisa has a 17.5% gain. Basic theory of management accounting is used, the hypothesis in this study that the percentage increase in the selling price set by Anisa Enterprises using mark-up wisdom greater than 17.5%Based on the results of the analysis and discussion:Cost of Production amplang with regard to the cost elements of the cost of production Raw material costs, Costs Direct Labor and Factory Overhead and General & Marketing costs resulting calculation of Cost of Production per day of Rp. 1,697,358, -.Cost of Production for 1 ounce size is Rp. 1,697,358, - 220 packs divided by Rp. 7715, -Price Mark-Up in theory = Rp. 7715 + (Rp. 7,715, - x 17.5%) = Rp. 9065, - Price Mark-Up according to calculations greater than 10,000, - according to calculations by the company or by 29.6% of the cost of production.The hypothesis put forward earlier that allegedly setting the selling price set by the Business amplang Anisa already give a greater profit margin of 17.5% accepted on the grounds that the selling price set Anisa Enterprises is Rp. 10,000, - above the cost of production and the price mark-up is 29.6% of the cost of production amplang, while the results of calculations using the selling price Mark-Up 17.5% obtained Mark-Up selling price of Rp. 9065, -. This means that dikenakkan Mark-Up by Anisa Enterprises in the sale price amplangnya benefit greater than 17.5%.